Depression Consultation Expert System - Minh Anh, Nguyen Thi (Universiti Teknologi Petronas, 2006)
Depression Consultation Expert System (DECES) is a web-based Diagnosis and Counseling system for depression cases based on knowledge from human expert. Given the shortage of psychiatrists, the refusal of patients on face-to-face consultation due to shyness, appointment hassles, time& cost of each treatment, and a considerable increase in numbers of depressive subjects, there is a definite sense of urgency in the development of this system. The objectives of the project are to understand the underlying concepts of AI in medicine in general and psychology in particular, and to develop DECES through research on diagnostic expert system, its construction techniques and approaches. The methodology used is expert system development life cycle with prototyping. The development begins with knowledge acquisition, then design of the knowledge base and inference methods. Application of this methodology allows the prototype to be evaluated and refined by professionals in stages to verify its credibility, reliability and clinical acceptability. The system is able to guide its users to a diagnosis process of identifying their depression levels and causes and getting self-help without the intervention of psychiatrists. The proposed system captures the expertise, which empowers patients with the ability to help themselves in depression treatment quickly, at any convenient place and time. With the increase recognition of the seriousness of depression and the importance to reduce it critically, the future depression expert system appears to be promising and optimistic. This paradigm shift makes depression consultation expert system an emerging and ever-evolving one that can be and should be productively explored.